El cuidado enfermero frente al dolor del prematuro hospitalizado en el servicio de neonatología I. Hospital Regional Lambayeque. Chiclayo - Yaipen Torres, Ana Victoria (2019)
The present quantitative investigation of correlational descriptive type, had like purpose to determine the relation between the nursing care and the pain of the hospitalized premature one. The sample universe was made up of a total of 17 health nurses. The data collection was carried out with the application of two instruments: questionnaire to measure the care in the management of pain in the neonatal hospitalized in the neonatology service, intermediate, of the Lambayeque Regional Hospital applied to 17 nurses, and the assessment scale of neonatal pain PIPP applied to 17 hospitalized preterm infants. The following results were obtained: The level of care of nurses is high with 47.1% and regular with 41.2%; 70.6% of premature infants do not suffer pain during their hospitalization. There is a direct relationship between nursing care and pain, stating that the higher the quality of care, the lower the presence of pain in a premature infant. For the statistical analysis, the criterion independence test (chi square) was applied, demonstrating that there is a highly significant relationship between nursing care and premature neonatal pain, p = 0.00.